Lindsaea linduensis (Lindsaeaceae, Polypodiales), a new fern species from Sulawesi, Indonesia - Cicuzza, Daniele; Kessler, Michael (Phytotaxa, 2012)
Lindsaea linduensis (Lindsaeaceae), from Central Sulawesi, Indonesia, is described as new to science. It differs from L. repens var. sessilis by having 2-pinnate fronds (versus 1-pinnate), longer petioles (10–17 cm versus 1–5 cm), and more widely spaced ultimate segments (>5 mm apart versus <4 mm). We provide an updated key to the species group to which this species belongs.